Upaya Meningkatkan Prestasi Belajar Melalui Model Pembelajaran Snowball Throwing Pada Mata Pelajaran Akidah Akhlak Kelas VIII MTs Al-Washliyah Pangkalan Brandan - Sri Lestari, Syahrul Kodrah, Zaifatur Ridha (LPPPI Publishing, 2023)
Based on observations made by researchers in class VIII of Al-Washliyah Pangkalan Brandan Private MTs, information was obtained, namely the low level of learning motivation of class VIII students in the Akidah Akhlak study field which can be seen from the average score of students who are under the Minimum Completeness Criteria (KKM). ie as many as 20 students still get an incomplete score and 10 students get a minimum completeness of ? 70. The application of the learning model is still not optimal because learning is carried out only by using the lecture method and giving assignments and questions and answers. Thus resulting in not maximal effort of teachers to increase student motivation. Teachers in the Akidah Akhlak study field have not directed students to student-centered learning (student oriented) so that indicators in increasing student learning motivation are hampered by learning activities that do not fully develop student creativity in learning, especially in forming students' abilities in critical thinking. The method used by researchers is Classroom Action Research which uses a cyclical reflection system consisting of 3 (three) cycles to determine the increase in students' learning motivation. The results of this study are the application of the Snowball Throwing Learning Model in increasing student motivation in the field of Aqidah Akhlak studies for Class VIII MTs students. Private Al-Washliyah Pangkalan Brandan has been well implemented and there has been an increase since the beginning of the pre-cycle, namely the number of students who received an average completeness score of 53.78 students who received a complete score in the Akidah Akhlak study field, in Cycle I it increased to 67, 75 students who completed the Aqidah Akhlak learning activity on learning motivation material. In Cycle II the level of student completeness in learning the Aqidah Akhlak was 74.6 in Class VIII MTs. Private Al-Washliyah Pangkalan Brandan. Then analyzed from Cycle III the student completeness reached 83.7. Thus it can be concluded that the application of the Snowball Throwing learning model can increase student motivation in the field of Akidah Akhlak study.